Strategies Used by Mexican Fourth-Grade Elementary Students in Solving Additive Word Problems - Axel Dircio-Vargas; Javier García-García; Gerardo Salgado-Beltrán; Aloisius Loka Son (CV. Samuel Manurung and Co, 2025)
To improve children's arithmetic learning, it is important to understand the strategies they use when solving arithmetic problems and the obstacles they find in this process. So, the objective of this research is to identify the strategies used by a group of Mexican fourth grade elementary school students in solving additive verbal arithmetic problems. We used a framework where the main theoretical elements that guided the study were characterized: strategies, types of strategies, verbal arithmetic problems, and the semantic and syntactic structures of the additive problems. This qualitative research, with a descriptive scope, uses case study as a method. The study cases were seven students from an Elementary School Located in ​​Zumpango de Neri, Guerrero, Mexico. To collect data, Task-Based Interviews were used, that were applied to the case studies in November 2024. The results allowed the identification of four reflective strategies: identifies a relevant keyword; selects the appropriate operation; performs mental calculation; and decomposes a numerical factor. Additionally, three non-reflective strategies were identified: uses an inappropriate keyword; operates with given data; and answers without performing operations. Some of the case studies used more than one strategy when solving some of the proposed tasks. These results allow suggesting that in the classroom the personal strategies used by students must be assessed in order to identify those that are thoughtless to help students travel towards the use of reflexive strategies. This will be possible through designs that incorporate problems resolving such as a central activity in the classroom.